Vocacional choice and personality in university students with the Rorschach test - Martínez, Patricia (1999)
This study, carried out in 120 last year students of a privare university in Lima, focuses in rhe relationships berween personality and vocarional choice. The objecrive of rhe srudy was ro describe and compare rhe mosr significanr personality characrerisrics of srudenrs from four differenr academic programs: Engineering, Economics, Law and Educarion. The Rorschach Psychodiagnosric, coded and interprered according ro rhe Exner Comprehensive Sysrem was uscd for rhis purpose. Resulrs showed rhar, in spire of rhe common characrerisrics, rhe response tcndencies and sryles were different in rhe four groups, particularly in rhe Engineering, that showed a cognitive style significantly differcnt from the other groups.